2013
DOI: 10.1186/1757-2215-6-15
|View full text |Cite
|
Sign up to set email alerts
|

Optimized protocol for cryopreservation of human eggs improves developmental competence and implantation of resulting embryos

Abstract: BackgroundSuccessful egg cryopreservation has many potential benefits to a variety of patients. However, a superior standard protocol describing all aspects of oocyte cryopreservation has not yet been identified. Oocyte cryopreservation is still a technical challenge for many infertility clinics. To maintain satisfactory clinical outcomes, there is a need to develop an easy to use, yet efficient laboratory protocol. The present study was designed to examine if human embryos resulting from eggs frozen with an o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 44 publications
(72 reference statements)
2
22
0
1
Order By: Relevance
“…Similar to previous studies [ 1 - 7 ], the present study indicates that high survival rates can be obtained after eggs were cryopreserved with vitrification. Also, high blastocyst development and embryo implantation rates were obtained with the vitrified/warmed donor eggs.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Similar to previous studies [ 1 - 7 ], the present study indicates that high survival rates can be obtained after eggs were cryopreserved with vitrification. Also, high blastocyst development and embryo implantation rates were obtained with the vitrified/warmed donor eggs.…”
Section: Discussionsupporting
confidence: 90%
“…Egg cryopreservation has become one of the key assisted reproduction technologies (ART) in humans [ 1 - 7 ]. Successful egg cryopreservation has allowed for the establishment of frozen egg banks [ 8 - 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this regard, it has been suggested that the time should be less than 10 s [127]. On the other hand, a short equilibration time for oocytes in the vitrification solution results in low survival and blastocyst formation rates [128,129]. This observation suggests that, in the short protocol, intracellular water may not be completely replaced by CPAs in the oocytes after exposure to the vitrification solution, and may contribute to damage of some organelles inside the oocyte.…”
Section: Exposure To or Equilibration Of The Cryoprotectantsmentioning
confidence: 99%